2021
DOI: 10.1186/s12916-021-02015-3
|View full text |Cite
|
Sign up to set email alerts
|

A core outcome set for studies evaluating interventions to prevent and/or treat delirium for adults requiring an acute care hospital admission: an international key stakeholder informed consensus study

Abstract: Background Trials of interventions to prevent or treat delirium in adults in an acute hospital setting report heterogeneous outcomes. Our objective was to develop international consensus among key stakeholders for a core outcome set (COS) for future trials of interventions to prevent and/or treat delirium in adults with an acute care hospital admission and not admitted to an intensive care unit. Methods A rigorous COS development process was used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Pneumonia and surgical site infection at the sternum were the most common. Delirium is usually reversible, but is associated with longer hospitalization, worse prognosis, and increased mortality [17]. PC and delirium may be caused by decreased activities of daily living due to trunk suppression caused by delirium or, conversely, by a cytokine upsurge caused by PC, which may impair optimal oxygenation of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia and surgical site infection at the sternum were the most common. Delirium is usually reversible, but is associated with longer hospitalization, worse prognosis, and increased mortality [17]. PC and delirium may be caused by decreased activities of daily living due to trunk suppression caused by delirium or, conversely, by a cytokine upsurge caused by PC, which may impair optimal oxygenation of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Relief of patient (and family) distress motivates clinicians to intervene [21]; yet, these outcomes have been rarely measured in delirium intervention studies. This evidence-practice gap may soon be rectified by inclusion of 'emotional distress' in a new core outcome set for studies of interventions to prevent and/or treat delirium for adults in acute care [22]. Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Key Pointsmentioning
confidence: 99%
“…Thorough guidelines, statements, and core outcome sets for delirium have previously been produced using consensus methods 13 19–30 . For example, the Network for Investigation of Delirium: Unifying Scientists (NIDUS) 2020 Scientific Think Tank listed identifying etiologic subtypes of delirium as a priority 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Thorough guidelines, statements, and core outcome sets for delirium have previously been produced using consensus methods. 13 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 For example, the Network for Investigation of Delirium: Unifying Scientists (NIDUS) 2020 Scientific Think Tank listed identifying etiologic subtypes of delirium as a priority. 31 The think tank suggested that future studies should use standardized approaches to identify contributors to delirium, to incorporate biomarkers, and to use subtyping to guide targeted treatments.…”
Section: Introductionmentioning
confidence: 99%